High-performance stainless steel-based water electrolysis difunctional electrode and application thereof

By phosphating the stainless steel and introducing the ruthenium element, high-performance stainless steel-based electrolytic water dual-function electrodes were prepared, which solved the problems of high overpotential and single function during catalysis of stainless steel in the prior art, and achieved efficient water electrolysis and stable electrode performance.

CN119685847AActive Publication Date: 2025-03-25CHONGQING UNIV

Patent Information

Application Number
CN202411861022.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In the prior art, stainless steel is used for electrolytic water catalysis with high overpotential potential, and can only be used as a single functional catalyst, and it is difficult to meet the needs of industrial alkaline electrolytic water.

Method used

By phosphating the stainless steel and introducing the ruthenium element, high-performance stainless steel-based electrolytic dual-function electrodes were prepared. Phosphating treatment produces metal phosphides, improving the hydrophilicity and conductivity of the surface; the introduction of ruthenium elements reduces the overpotential and improves catalytic activity.

Benefits of technology

It significantly reduces the overpotential of hydrogen evolution reaction and oxygen evolution reaction, improves the electrochemical reaction rate and electrode stability and durability, and realizes the efficient performance of a dual-function catalyst. It is suitable for a variety of electrolytic water systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685847A_ABST
    Figure CN119685847A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance stainless steel-based electrolyzed water difunctional electrode and application thereof, and the electrode is prepared by the following steps: step 1, pretreating the surface of stainless steel to remove impurities on the surface of the stainless steel; 2, the stainless steel obtained after treatment in the step 1 and a phosphorus source are placed under the condition of 350-450 DEG C, the stainless steel is phosphatized for 1-3 h in the argon atmosphere, and a phosphatized stainless steel electrode is obtained; wherein the linear distance between the phosphorus source and the stainless steel is kept to be 5-10 cm; and 3, placing the phosphatized stainless steel electrode obtained in the step 2 in a RuCl3 solution, and carrying out electro-deposition by taking the phosphatized stainless steel as a cathode to obtain the electrode, wherein the concentration of the RuCl3 solution ranges from 2 mmol / L to 8 mmol / L, the potential window during electro-deposition ranges from-2 V to 0 V, and the electro-deposition time ranges from 15 circles to 25 circles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a high-performance stainless steel-based water electrolysis dual-function electrode and its application. Background Art

[0002] Driven by the global energy structure transformation and environmental protection, hydrogen energy, with its significant advantages such as high energy density, is regarded as the ultimate choice for the future energy system. Its large-scale application will have a significant impact on achieving a fundamental green transformation of the energy structure. As an environmentally friendly and resource-rich method of hydrogen production, water electrolysis is considered to be a key way to achieve green hydrogen production. However, water electrolysis involves two half reactions, hydrogen evolution and oxygen evolution, which often require a higher overpotential to drive, which not only increases the power consumption, but also limits the economy and competitiveness of water electrolysis hydrogen production technology.

[0003] Precious metal catalysts (Pt / C and RuO2) occupy a central position in industrial applications due to their ultra-low overpotential and excellent long-term stability. However, the scarcity and high cost of these materials make electrocatalytic water splitting an expensive hydrogen production process. Although nickel-based alloy catalysts have been used in alkaline water electrolysis processes, their performance still needs to be significantly improved. Therefore, the core task in the field of water electrolysis to produce hydrogen focuses on the development of low-cost and efficient catalysts, especially those based on elements with high earth abundance. The key strategies in this direction are two-fold: first, deeply explore the potential of non-precious metal materials as an effective substitute for precious metals; second, through precise control, add appropriate amounts of precious metals into the transition metal matrix to construct a composite catalyst, so as to achieve the optimal balance between cost-effectiveness and catalytic performance.

[0004] Stainless steel is inexpensive, abundant in source, has good conductivity, and is rich in active elements (Fe and Ni), and is considered an ideal catalytic material. In addition, the use of stainless steel as a water electrolysis electrode can not only reduce the cost of hydrogen production, but also eliminate the potential difference between the electrode and the stainless steel bipolar plate, thereby further improving the stability and service life of the electrolyzer. In view of this, stainless steel materials are increasingly attracting deep attention and high attention in the field of water electrolysis catalyst research. However, stainless steel without any treatment has poor catalytic performance and needs to be modified to meet the needs of industrial water electrolysis. The modification technology for stainless steel mainly focuses on two major directions: First, the stainless steel material is exposed to an oxidizing environment, and this environment is used to promote the in-situ generation of metal oxide and hydroxide layers with excellent oxygen evolution (OER) catalytic performance on the stainless steel surface. For example, patent CN116145180A discloses a surface modification method for stainless steel, in which stainless steel is subjected to hydrothermal corrosion treatment and hydrothermal sulfidation treatment to give the stainless steel surface good oxygen evolution catalytic activity. However, this method still has the following problems: (1) Improper treatment of the mixed corrosion solution composed of NaOH and NaCl and the NaS solution is likely to pollute the environment; (2) It is difficult to apply to large-scale industrial production, especially when treating large-sized stainless steel electrodes; (3) The electrocatalytic hydrogen evolution performance is poor, so it cannot be used as an efficient bifunctional catalyst. Second, other elements are introduced into the surface of stainless steel by a specific method, aiming to optimize and enhance the catalytic performance of stainless steel by means of element doping or the formation of new compounds. For example, patent CN 110093623 A discloses a preparation method for phosphated stainless steel material, in which stainless steel material and a phosphorus source are added to a sealed container and heated to obtain a phosphated stainless steel material. However, this method also has limitations: (1) Uneven diffusion may lead to uneven distribution of the phosphating layer on the stainless steel surface, affecting the overall performance and appearance of the material; (2) The electrocatalytic hydrogen evolution performance obtained by the one-step phosphating method is poor (current density is 100mA / cm 2 The overpotential is as high as 325 mV, so it cannot be used as an efficient perhydrolysis catalyst.

[0005] Although existing technologies have improved the OER catalytic performance through surface modification methods such as oxidation and sulfidation, the hydrogen evolution overpotential of stainless steel materials remains high, seriously restricting their widespread application in the field of hydrogen production by water electrolysis. Summary of the invention

[0006] In view of the above-mentioned deficiencies in the prior art, the purpose of the present application is to provide a high-performance stainless steel-based bifunctional water electrolysis electrode and its application, so as to solve the problems in the prior art that stainless steel has a high overpotential when used for water electrolysis catalysis, can only be used as a single-function catalyst, and is difficult to meet the needs of industrial alkaline water electrolysis.

[0007] In order to solve the above technical problems, this application adopts the following technical solutions:

[0008] A high-performance stainless steel-based water electrolysis bifunctional electrode, the electrode is prepared by the following steps:

[0009] Step 1: Pre-treat the stainless steel surface to remove impurities on its surface;

[0010] Step 2: placing the stainless steel and the phosphorus source obtained after the treatment in step 1 at 350-450° C. respectively, in an argon atmosphere, phosphating the stainless steel for 1-3 hours to obtain a phosphated stainless steel electrode; wherein the linear distance between the phosphorus source and the stainless steel is maintained at 5-10 cm; and the mass ratio of the phosphorus source to the stainless steel is 2-3;

[0011] Step 3: placing the phosphated stainless steel electrode obtained in step 2 in a RuCl3 solution, and performing electrodeposition using the phosphated stainless steel as a cathode to obtain the electrode; wherein the concentration of the RuCl3 solution is 2 to 8 mmol / L, the potential window during electrodeposition is -2 to 0 V, and the electrodeposition time is 15 to 25 cycles.

[0012] Preferably, calculated by mass percentage, in the stainless steel, the Cr content is greater than 5%, and the Ni content is greater than 5%.

[0013] Preferably, the stainless steel comprises the following components calculated by mass percentage:

[0014] Cr is 16-18%, Ni is 10-14%, Si is 2-3%, Mn is 0-2%, and the balance is Fe.

[0015] Preferably, in step 1, the stainless steel is pickled with dilute sulfuric acid; the concentration of the dilute sulfuric acid is 1 to 2 mol / L, and the pickling time is 10 to 20 min.

[0016] Preferably, in step 2, the stainless steel and the phosphorus source are placed in a tubular furnace respectively, and the phosphorus source is located upstream of the stainless steel in the tubular furnace, so that the substance obtained by decomposing the phosphorus source at high temperature can react with the stainless steel.

[0017] Preferably, in step 2, the heating rate is 1-3°C / min.

[0018] Preferably, the phosphorus source is one of NaH2PO2 and KH2PO2, or a mixture of the two.

[0019] Preferably, during the electrodeposition process of step 3, the stainless steel electrode is turned over after 10 cycles of electrodeposition, and then electrodeposition is performed for another 10 cycles.

[0020] The present application also provides an application of a high-performance stainless steel-based water electrolysis bifunctional electrode, wherein the electrode is used for electrolyzing water and simultaneously evolving hydrogen and oxygen.

[0021] Compared with the prior art, this application has the following beneficial effects:

[0022] 1. In the present application, metal phosphides (such as FeP4 and Ni2P, etc.) are generated in situ on the surface of stainless steel by phosphating stainless steel. These phosphides not only improve the hydrophilicity of the stainless steel surface, but also introduce new active sites, promote the adsorption and dissociation of water molecules, thereby improving the efficiency of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER); at the same time, the metal phosphides form a uniform conductive layer on the surface of stainless steel, which significantly improves the conductivity of the electrode, helps to increase the current density, reduce resistance loss, and thus improve the overall efficiency of water electrolysis; moreover, these phosphide layers are very stable on the surface of stainless steel, increase the corrosion resistance and stability of the electrode, and can extend the service life of the electrode, especially in alkaline environments, where the stability of the electrode is particularly important.

[0023] 2. The present application introduces ruthenium (Ru) onto the surface of stainless steel by electrodeposition. Ruthenium is a highly efficient electrocatalyst that can significantly reduce the overpotential of HER and OER and increase the electrochemical reaction rate. The addition of ruthenium undoubtedly further enhances the catalytic activity of the electrode. In addition, the introduction of ruthenium also adjusts the electronic structure of the transition metal phosphide, optimizes its catalytic performance, and can effectively prevent the electrode from being degraded or inactivated during long-term use. The synergistic effect between ruthenium and phosphide further enhances the durability of the electrode.

[0024] 3. The present application optimizes the preparation process. During the electrodeposition process, the stainless steel electrode is flipped after 10 cycles of deposition and then subjected to 10 cycles of deposition. This operation ensures the uniform distribution of ruthenium elements on the electrode surface, avoids the problem of local uneven deposition, and further increases the electrochemical active area (ECSA). A larger ECSA means that more active sites participate in the reaction, thereby improving the catalytic efficiency. At the same time, the preparation method described in the present application includes three main steps: pretreatment, phosphating and electrodeposition. The whole process is relatively simple and easy to operate. Compared with the traditional multi-step synthesis method, the present application reduces the complex pre-treatment and post-treatment steps and reduces the process complexity. Moreover, both phosphating and electrodeposition are carried out under relatively mild conditions, without the need for extreme temperature or pressure, thereby reducing energy consumption and equipment requirements. In particular, in the phosphating treatment, the reaction temperature is controlled between 350 and 450°C, which is much lower than some high-temperature synthesis methods, further saving energy. More importantly, the stainless steel substrate material used in the present application is inexpensive and easy to obtain, and the phosphorus source (such as NaH2PO2, KH2PO2) and the ruthenium source (RuCl3) are also easily available raw materials. Combined with simple phosphating and electrodeposition technology, the cost of the entire preparation process is greatly reduced, and it has a good industrial prospect.

[0025] 4. The electrode described in the present application is a bifunctional electrode, which has excellent HER and OER performance at the same time, and can achieve efficient water electrolysis on the same electrode, which is particularly important for a full water decomposition device (i.e., an electrolyzer that simultaneously produces hydrogen and oxygen), and can simplify system design, reduce costs, and improve overall energy conversion efficiency; moreover, since the electrode has good stability and high-efficiency catalytic performance, it is suitable for a variety of water electrolysis systems, including alkaline electrolytes, neutral electrolytes, and acidic electrolytes, which makes the electrode perform well in different application scenarios and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a scanning electron microscope photo of stainless steel without any treatment.

[0027] Figure 2 This is a scanning electron microscope photograph of the stainless steel electrode obtained in Comparative Example 1 of the present invention.

[0028] Figure 3 This is a scanning electron microscope photograph of the stainless steel electrode obtained in Example 1 of the present invention.

[0029] Figure 4 This is a transmission electron microscope photograph of the stainless steel electrode obtained in Example 1 of the present invention.

[0030] Figure 5 It is the wetting angle of the stainless steel without any treatment and the stainless steel electrode obtained in Comparative Example 1 of the present invention.

[0031] Figure 6 : The wetting angles of the stainless steel electrodes obtained in Example 1 of the present invention and Comparative Example 2.

[0032] Figure 7 HER performance of stainless steel without any treatment, comparative example 1 of the present invention, comparative example 2 and comparative example 3.

[0033] Figure 8 The OER performance of stainless steel without any treatment, comparative example 1 of the present invention, comparative example 2 and comparative example 3.

[0034] Fig. 9 The electrochemical impedance spectra of stainless steel without any treatment, comparative example 1 of the present invention, comparative example 2 and comparative example 3 are shown.

[0035] Fig.10 The cyclic voltammetry curves are for stainless steel without any treatment, comparative example 1 of the present invention, comparative example 2 and comparative example 3.

[0036] Fig.11 The electrochemical specific surface area spectra of stainless steel without any treatment, comparative example 1 of the present invention, comparative example 2 and comparative example 3.

[0037] In the figure, PSS is comparative example 1, Ru-SS is comparative example 2, Ru-PSS is an embodiment, and SS is a control sample. DETAILED DESCRIPTION

[0038] This application will combine the drawings in the embodiments of this application to clearly and completely describe the technical solutions in the embodiments of this application. Obviously, the described embodiments are only part of the embodiments of this application, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on this application belong to the scope of protection of this application.

[0039] Unless otherwise indicated in specific cases in this application, the numerical ranges listed herein include the upper and lower limits, as well as all integers and fractions within the range, and are not limited to the specific values ​​listed when defining the range.

[0040] 1. A high-performance stainless steel-based dual-function electrode for water electrolysis

[0041] The electrode described in this application is prepared by the following steps:

[0042] Step 1: Pre-treat the stainless steel surface to remove impurities on its surface;

[0043] Step 2: placing the stainless steel obtained after the treatment in step 1 and the phosphorus source at 350-450° C. respectively, phosphating the stainless steel for 1-3 hours to obtain a phosphated stainless steel electrode; wherein the linear distance between the phosphorus source and the stainless steel is maintained at 5-10 cm; and the mass ratio of the phosphorus source to the stainless steel is 2-3;

[0044] Step 3: placing the phosphated stainless steel electrode obtained in step 2 in a RuCl3 solution, and performing electrodeposition using the phosphated stainless steel as a cathode to obtain the electrode; wherein the concentration of the RuCl3 solution is 2 to 8 mmol / L, the potential window during electrodeposition is -2 to 0 V, and the electrodeposition time is 15 to 25 cycles.

[0045] Based on the problem that stainless steel in the prior art has high overpotential when used for electrolysis of water, can only be used as a single functional catalyst, and is difficult to meet the needs of industrial alkaline electrolysis of water, the present application conceives a functional design of stainless steel-based electrodes, aiming to improve the efficiency of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in the process of water electrolysis, and enhance its stability and durability. To this end, the present application considers phosphating the unmodified, and using the chemical reaction between the phosphorus source and the stainless steel at a specific temperature, the iron and nickel elements on the surface of the stainless steel are in situ phosphated into FeP4 and Ni2P, which have certain OER and HER catalytic activity. This phosphating treatment not only improves the hydrophilicity of the stainless steel surface, which enables the bubbles generated on the stainless steel surface to escape in time, which is conducive to the catalytic reaction; it also forms a heterogeneous structure of FeP4 and Ni2P, which has a rich interface and can provide more active sites, so that the formed phosphating layer is used as a conductive layer, which improves the conductivity of the electrode; compared with unphosphated stainless steel, the phosphating electrode has significantly improved catalytic performance and stability, especially in an alkaline environment. Secondly, the present application considers introducing ruthenium element, because the present application found during the research that introducing ruthenium (Ru) into the phosphated stainless steel surface by electrodeposition can reduce the overpotential of HER and OER, thereby increasing the electrochemical reaction rate; moreover, the synergistic effect between ruthenium and phosphide can also adjust the electronic structure of phosphide, further optimize the catalytic performance and prevent electrode degradation or inactivation. This combination not only enhances the catalytic activity of the electrode, but also improves its durability.

[0046] In some embodiments of the present application, in step 2, the phosphating temperature is controlled between 350 and 450°C. When the temperature is too high, the surface of the phosphating layer on the surface of the stainless steel is rough, forming a loose or defective film layer, which reduces its corrosion resistance and adhesion; when the temperature is too low, the phosphorus source cannot be completely decomposed, and the metal elements on the surface of the stainless steel cannot be fully phosphated. Therefore, the phosphating temperature can be 350°C, 400°C, 450°C, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges in other embodiments.

[0047] In some embodiments of the present application, in step 2, the phosphating time is controlled between 1 and 3 hours. If the time is too short, too little metal phosphide will be generated in situ on the stainless steel surface, which will not improve the electrode performance; and if the time is too long, the generated metal phosphide will accumulate, which is not conducive to improving the performance of the electrode. Therefore, the phosphating time can be 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges in other embodiments.

[0048] In some embodiments of the present application, in step 2, the linear distance between the phosphorus source and the stainless steel is maintained at 5 to 10 cm. If the two are too close together, the metal phosphide grown in situ on the surface of the stainless steel will be uneven; and if they are too far apart, it will be unfavorable for the growth of the phosphide. Therefore, the linear distance between the phosphorus source and the stainless steel can be 5 cm, 6 cm, 7 cm, 8 cm, 9 cm, 10 cm, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges in other embodiments.

[0049] In some embodiments of the present application, in step 2, the mass ratio of the phosphorus source to the stainless steel is 2 to 3. If the amount of the phosphorus source is too little, the metal elements on the surface of the stainless steel will not be fully phosphated; and if the amount of the phosphorus source is too much, the excess phosphorus source will be blown to the surface of the stainless steel by argon gas, thereby contaminating the sample. Therefore, the mass ratio of the phosphorus source to the stainless steel can be 2:1, 2.5:1, 3:1, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges in other embodiments.

[0050] In some embodiments of the present application, the concentration of the RuCl3 solution is between 2 and 8 mmol / L. If the concentration is too low, it is difficult for the Ru element to be deposited on the stainless steel electrode, and if the concentration is too high, it will cause the Ru element to accumulate.

[0051] In some embodiments of the present application, the Cr content in the stainless steel is greater than 5%, and the Ni content is greater than 5%, calculated by mass percentage. The present application is applicable to almost all stainless steels with a Ni mass fraction greater than 5%. When the Ni content in the stainless steel is low, Ni2P cannot be formed on the electrode surface. Further preferably, the stainless steel comprises the following components, calculated by mass percentage: Cr is 16-18%, Ni is 10-14%, Si is 2-3%, Mn is 0-2%, and the balance is Fe.

[0052] In some embodiments of the present application, in step 1, the stainless steel is pickled with dilute sulfuric acid; the concentration of dilute sulfuric acid is 1-2 mol / L, and the pickling time is 10-20 min. The function of dilute sulfuric acid is to remove rust and impurities on the surface of stainless steel to prevent it from affecting the effect of subsequent annealing treatment, so the concentration of dilute sulfuric acid is not easy to be too high, which will cause excessive corrosion of stainless steel, and further annealing will have an adverse effect; the concentration is not easy to be too low, and too low will not have a cleaning effect. The concentration of dilute sulfuric acid can be 1 mol / L, 1.5 mol / L, 2 mol / L, etc., and all ranges and sub-ranges between the above values; the pickling time can be controlled at 10 min, 15 min, 20 min, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiment, any of the above ranges can be combined with any other ranges in other embodiments.

[0053] In some embodiments of the present application, in step 2, the stainless steel and the phosphorus source are respectively placed in a tubular furnace, and the phosphorus source is located upstream of the stainless steel in the tubular furnace, so that when the upstream phosphorus source is decomposed at high temperature, the substance produced can flow in the direction of the air flow in the furnace, so that the substance obtained by decomposing the phosphorus source at high temperature can react with the stainless steel.

[0054] In some embodiments of the present application, in step 2, the heating rate is 1 to 3°C / min. Controlling the heating rate can ensure stable and continuous decomposition of the phosphorus source. If the heating rate is too slow, the reaction efficiency will be reduced and the energy consumption will increase; and if the heating rate is too fast, the phosphorus source will decompose too fast, resulting in it being unable to fully react with the metal elements on the surface of the stainless steel to form a sufficient amount of metal phosphide. Therefore, the heating rate can be 1°C / min, 2°C / min, 3°C / min, etc., and all ranges and sub-ranges between the above values. It should be understood that in the embodiments, any of the above ranges can be combined with any other ranges in other embodiments.

[0055] In some embodiments of the present application, the phosphorus source is one of NaH2PO2 and KH2PO2 or a mixture of the two. In the present application, one of NaH2PO2 and KH2PO2 or a mixture of the two is preferred. If other phosphorus sources are used, it is easy to produce unnecessary side reactions, which in turn causes the stainless steel surface to be contaminated by byproducts, so that the performance of the stainless steel electrode is adversely affected.

[0056] In some embodiments of the present application, during the electrodeposition process of step 3, the stainless steel electrode is flipped after 10 cycles of deposition, and then electrodeposition is performed for another 10 cycles to ensure uniform distribution of ruthenium elements on the electrode surface, increase the electrochemical active area (ECSA), and thereby improve the catalytic efficiency.

[0057] In some embodiments of the present application, in step 3, the potential window during electrodeposition is -1.5V to 0.5V. If the potential window is too small, it may not cover the formation potential range of the target deposit, resulting in a reduced deposition rate and slow growth of the deposited layer, thereby reducing the overall deposition efficiency. If the potential window is too large, it will not only increase energy consumption, but also affect the stability of the deposition process. Therefore, the potential window during electrodeposition can be -1.5 to -0.5V, -2.0 to -1V, -1 to 0V, etc., and all ranges and sub-ranges between the above values. During electrodeposition treatment, the deposition time is controlled to be 15 to 25 turns. If the deposition time is too short, the amount of deposition on the stainless steel electrode material will be insufficient, and the short-term deposition may not form a complete and dense sediment structure. Too long a deposition time not only increases energy consumption, but also may cause more side reactions, affecting the catalytic performance of the stainless steel electrode. Therefore, the deposition time is preferably 20 turns, which can be 15 turns, 20 turns, 25 turns, etc., and all ranges and sub-ranges between the above values. It should be understood that in embodiments, any of the above ranges may be combined with any other ranges in other embodiments.

[0058] 2. Application of a high-performance stainless steel-based dual-function electrode for water electrolysis

[0059] The above electrode is used for alkaline water electrolysis and simultaneous hydrogen and oxygen evolution. In the process of water electrolysis, it can be used as an anode for oxygen evolution and as a cathode for hydrogen evolution.

[0060] 3. Examples and Comparative Examples

[0061] Example 1

[0062] Step 1: Pretreatment of stainless steel materials

[0063] Take 316L foam stainless steel, cut it into rectangles, polish the stainless steel surface with 500-grit sandpaper for 5 minutes, then soak it in 1 mol / L dilute sulfuric acid solution for 20 minutes, slowly rinse it with deionized water for 3 minutes and dry it for 6 hours to obtain a rectangular stainless steel sheet.

[0064] Step 2: Preparation of phosphated stainless steel electrodes

[0065] The stainless steel treated in step 1 is placed in a tubular furnace. Under an argon atmosphere, 2 g of NaH2PO2 is placed upstream of the tubular furnace as a phosphorus source, and the stainless steel is placed downstream of the tubular furnace for annealing for 2 hours to obtain an annealed stainless steel electrode; wherein the phosphating temperature is 400°C and the heating rate is 5°C / min; and the distance between the phosphorus source and the stainless steel crucibles is maintained at 5 to 10 cm.

[0066] Step 3: Preparation of bifunctional stainless steel electrodes

[0067] The stainless steel electrode treated in step 2 is placed in a RuCl3 electrolyte, and the stainless steel is used as a cathode for electrodeposition to obtain the stainless steel bifunctional electrode; wherein the concentration of RuCl3 in the electrolyte is 5 mmol / L, the potential window during electrodeposition is -1.5 to 0.5 V, and the electrodeposition time is 20 cycles.

[0068] Example 2

[0069] An improvement is made on the basis of Example 1, except that in step 2, the mass of NaH2PO2 is 1.5 g.

[0070] Example 3

[0071] An improvement is made on the basis of Example 1, except that in step 2, the mass of NaH2PO2 is 2.5 g.

[0072] Example 4

[0073] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 2, the phosphating temperature is 350°C.

[0074] Example 5

[0075] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 2, the phosphating temperature is 450°C.

[0076] Example 6

[0077] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the potential window is -2.0 to -1.0V.

[0078] Example 7

[0079] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the potential window is -1.0 to 1.0V.

[0080] Example 8

[0081] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the deposition time is 15 cycles.

[0082] Example 9

[0083] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the deposition time is 25 cycles.

[0084] Comparative Example 1

[0085] An improvement is made on the basis of Example 1, and the difference therefrom is that the processing of step 3 is not performed.

[0086] Comparative Example 2

[0087] An improvement is made on the basis of Example 1, which differs from the embodiment 1 in that the treatment in step 2 is not performed, and the stainless steel obtained by the treatment in step 1 is directly processed in step 3.

[0088] Comparative Example 3

[0089] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 2, the phosphating temperature is 300°C.

[0090] Comparative Example 4

[0091] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 2, the phosphating temperature is 500°C.

[0092] Comparative Example 5

[0093] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the electrodeposition time is 10 cycles.

[0094] Comparative Example 6

[0095] An improvement is made on the basis of Example 1, and the difference therefrom is that in step 3, the electrodeposition time is 30 cycles.

[0096] 3. Performance Analysis

[0097] 1. Catalyst micromorphology

[0098] The stainless steel samples of the embodiment and the untreated stainless steel (control sample) were placed on a JSM-7800F scanning electron microscope and a Talos F200S transmission electron microscope produced by JEOL Ltd. (JEOL) for microscopic morphology observation. Figure 1 and Figure 2 It can be seen that the surface of the stainless steel without any treatment is relatively smooth, with a few irregular textures, small holes and particles; the surface of the stainless steel electrode of Comparative Example 1 after annealing shows a phosphide flake structure. These structures are intertwined to form a complex three-dimensional network structure, which shows that the phosphating film has good adhesion and coverage. At the same time, the bonding force between the phosphating film and the substrate is very strong and not easy to fall off and peel off, which provides an ideal underlying structural support for subsequent electrodeposition.

[0099] Depend on Figure 3 It can be seen that after the electroplating treatment of phosphating stainless steel, the surface of the stainless steel in Example 1 still shows an interwoven flaky structure. Figure 4The transmission electron micrograph also shows that the active material on the surface of the stainless steel electrode of Example 1 presents a stacked sheet structure, which indicates that the structure of the phosphating film is not destroyed by the electrodeposition process, but continues to maintain its integrity, which indicates that the structure on the surface of the stainless steel in Example 1 has good thermal stability and chemical stability.

[0100] 2. Determination of overpotential

[0101] The embodiments and comparative examples, as well as stainless steel (control sample) without any treatment, were placed on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. to measure the LSV curve. A three-electrode system was used to test the hydrogen and oxygen evolution performance, with a stainless steel electrode as the anode, a graphite rod as the cathode, Hg / HgO as the reference electrode, and a 1 mol / L KOH solution as the electrolyte. This method is different from the third step of electrodeposition.

[0102] Table 1 Overpotential measurement results (HER) of different stainless steel-based electrodes

[0103]

[0104] Table 2 Overpotential measurement results of different stainless steel-based electrodes (OER)

[0105]

[0106]

[0107] Depend on Figures 7-8 From Tables 1 and 2, we can see that:

[0108] (1) In terms of hydrogen reaction (HER) performance:

[0109] At 10mA / cm 2 At a current density of , the overpotential of the embodiment is significantly lower than that of all comparative examples and the control sample, which indicates that the embodiment has a lower starting potential, meaning that the embodiment can start an effective hydrogen evolution reaction at a lower voltage.

[0110] At 500mA / cm 2 and 1000mA / cm 2 At a current density of , the overpotential of the embodiment is also significantly lower than that of the comparative example and the control sample, which indicates that the embodiment still maintains a relatively high catalytic efficiency at a high current density and can effectively reduce energy consumption.

[0111] (2) In terms of oxygen evolution reaction (OER) performance:

[0112] For 10mA / cm 2The current density of Examples 1 to 9 is in the range of 266-279 mV, while the overpotential range of Comparative Examples 1 to 6 is 275-310 mV, and the overpotential of the control sample is 308 mV. The overpotential of the embodiments is slightly higher than that of some comparative examples, but is still at a relatively low level overall. Although the difference is not large, in this case, the relatively low overpotential of the embodiments still helps to improve the reaction efficiency.

[0113] At 500mA / cm 2 and 1000mA / cm 2 At a current density of , the overpotential of the embodiment is significantly lower than that of the comparative example and the control sample, which indicates that the embodiment exhibits better OER performance at high current density and can effectively reduce energy consumption and increase the reaction rate.

[0114] (3) Comprehensive advantages:

[0115] Whether it is HER or OER, the overpotential of the embodiment at different current densities is significantly lower than that of the comparative example and the control sample, showing higher catalytic activity, which indicates that the embodiment can achieve efficient water electrolysis at a lower voltage, thereby improving energy conversion efficiency. Since the embodiment adopts phosphating treatment and the introduction of ruthenium elements, these improvement measures not only improve the catalytic performance of the electrode, but also enhance its stability and durability; especially for long-term operation of electrolyzers, stable electrode performance is crucial. From low to high current density, the embodiment shows good performance, which means that it is suitable for a wider range of application scenarios, including but not limited to small laboratory equipment, industrial-scale water electrolysis devices, etc.

[0116] 3. Electrochemical impedance spectroscopy

[0117] The examples and comparative examples, as well as stainless steel without any treatment (control sample), were placed on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. to measure electrochemical impedance spectroscopy (EIS).

[0118] Table 3 Electrochemical impedance spectroscopy results of different stainless steel-based electrodes

[0119] Sample name Electrochemical impedance(Ω) Comparative Example 1 0.38 Comparative Example 2 0.41 Comparative Example 3 0.66 Comparative Example 4 0.42 Comparative Example 5 0.54 Comparative Example 6 0.39 Example 1 0.28 Example 2 0.26 Example 3 0.32 Example 4 0.33 Example 5 0.27 Example 6 0.28 Example 7 0.32 Example 8 0.30 Example 9 0.35 Control 0.44

[0120] Depend on Fig. 9 From Table 3 we can see that:

[0121] (1) As can be seen from Table 2, the electrochemical impedance range of Examples 1 to 9 is 0.26-0.35Ω, the electrochemical impedance range of Comparative Examples 1 to 6 is 0.38-0.66Ω, and the electrochemical impedance of the stainless steel without any treatment (control sample) is 0.44Ω; this indicates that after the phosphating treatment and the introduction of ruthenium element in the examples, the conductivity of the stainless steel-based electrode is significantly improved, and the resistance loss is small; compared with the examples, the electrochemical impedance of the comparative examples is generally higher, which indicates that the comparative examples may encounter greater resistance losses during the electrolysis process, resulting in reduced energy conversion efficiency; and the control examples further confirm the deficiencies of the untreated stainless steel in terms of conductivity and catalytic activity.

[0122] (2) From Fig. 9 It can be seen that the Nyquist plots obtained from the electrochemical impedance spectroscopy test of the stainless steel-based bifunctional water electrolysis electrode prepared in the embodiment and the comparative example and the stainless steel without any treatment are both approximately semicircular. The smaller the radius of the semicircle of the Nyquist plot (i.e., the impedance plot), the lower the impedance of the material.

[0123] (3) The electrochemical impedance of the embodiment is significantly lower than that of the comparative example and the control sample, which indicates that the embodiment can conduct current more effectively and reduce resistance loss during water electrolysis; lower resistance loss helps to improve electrolysis efficiency, reduce energy consumption, and improve the performance of the overall system. At the same time, the phosphating treatment forms a uniform conductive layer on the surface of the stainless steel, which significantly improves the conductivity of the electrode; moreover, the introduction of ruthenium not only enhances the catalytic activity, but also adjusts the electronic structure of the transition metal phosphide, further optimizing the conductive properties of the electrode; finally, due to the lower electrochemical impedance, the embodiment can achieve a higher current density under the same working conditions, thereby improving the efficiency of water electrolysis, and lower resistance loss also means less heat generation, which helps to maintain the stable operation of the system and extend the service life of the electrode.

[0124] 4. Determination of electrochemical specific surface area

[0125] The examples and comparative examples, as well as stainless steel (control sample) without any treatment, were placed on a CHI1140C electrochemical workstation produced by Shanghai Chenhua Instrument Co., Ltd. to measure cyclic voltammetry curves (CV curves). The electrochemical specific surface area (C dl ).

[0126] Table 4 Electrochemical specific surface area determination results of different stainless steel-based electrodes

[0127] Sample name <![CDATA[Electrochemical specific surface area (mF·cm -2 )]]> Comparative Example 1 22.5 Comparative Example 2 9.4 Comparative Example 3 12.2 Comparative Example 4 25.2 Comparative Example 5 25.5 Comparative Example 6 29.6 Example 1 44.8 Example 2 36.8 Example 3 38.3 Example 4 42.5 Example 5 44.3 Example 6 43.6 Example 7 40.2 Example 8 43.7 Example 9 42.2 Control 4.7

[0128] From Table 4 and Figures 10-11 It can be seen that:

[0129] (1) As can be seen from Table 4, the ECSA range of Examples 1 to 9 is 36.8-44.8 mF·cm-2, which indicates that after phosphating and the introduction of ruthenium, the surface activity of the stainless steel-based electrode is significantly increased, providing more active sites; the ECSA range of Comparative Examples 1 to 6 is 9.4-29.6 mF·cm-2. Compared with the examples, the ECSA of the comparative examples is generally lower, which means that they have fewer active sites that can participate in the reaction under the same conditions and the catalytic efficiency is relatively low; moreover, both Comparative Examples 1 and 2 only carry out one step in the method described in the present application, which shows that such treatment has a very limited effect on the improvement of the electrochemical specific surface area; and the ECSA of the stainless steel (control sample) without any treatment is only 4.7 mF·cm-2, which is much lower than all the examples and most of the comparative examples, which further confirms that the untreated stainless steel has a very limited ability to provide active sites.

[0130] (2) The ECSA of the embodiment is significantly higher than that of the comparative example and the control sample, which indicates that the embodiment has more surface active sites and can more effectively adsorb and dissociate water molecules, thereby improving the catalytic efficiency of hydrogen evolution reaction (HER) and oxygen evolution reaction (OER); more active sites also mean a larger reaction interface, which helps to improve the current density and reaction rate. This also further proves that the phosphating treatment generates metal phosphides (such as FeP4, Ni2P, etc.) on the surface of stainless steel. These phosphides not only improve the surface hydrophilicity, but also introduce new active sites; the introduction of ruthenium also enhances the catalytic activity of the electrode and optimizes the catalytic performance. This combination enables the embodiments to exhibit higher catalytic efficiency in the HER and OER processes; finally, since the embodiments have higher ECSA, they can achieve higher current density at the same voltage, thereby improving the overall efficiency of water electrolysis, and more active sites also help to reduce overpotential, reduce energy consumption, and improve the energy conversion efficiency of the system; at the same time, the embodiments not only improve the catalytic activity through phosphating treatment and the introduction of ruthenium, but also enhance the stability and durability of the electrode, especially in the long-term operation process, more active sites can effectively prevent electrode degradation or inactivation, and extend the service life of the electrode; high ECSA makes the embodiments suitable for a variety of water electrolysis systems, including alkaline, neutral and acidic electrolytes. This wide applicability enables the embodiments to perform well in different application scenarios and has broad application prospects.

[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the technical solution. Ordinary technicians in this field should understand that those modifications or equivalent substitutions of the technical solution of the present application that do not depart from the purpose and scope of the technical solution of the present application should be included in the scope of the claims of the present application.

Claims

1. A high-performance stainless steel-based water electrolysis bifunctional electrode, characterized in that: The electrode is prepared by the following steps: Step 1: Pre-treat the stainless steel surface to remove impurities on its surface; Step 2: placing the stainless steel and the phosphorus source obtained after the treatment in step 1 at 350-450° C. respectively, in an argon atmosphere, phosphating the stainless steel for 1-3 hours to obtain a phosphated stainless steel electrode; wherein the linear distance between the phosphorus source and the stainless steel is maintained at 5-10 cm; and the mass ratio of the phosphorus source to the stainless steel is 2-3; Step 3: placing the phosphated stainless steel electrode obtained in step 2 in a RuCl3 solution, and performing electrodeposition using the phosphated stainless steel as a cathode to obtain the electrode; wherein the concentration of the RuCl3 solution is 2 to 8 mmol / L, the potential window during electrodeposition is -2V to 0V, and the electrodeposition time is 15 to 25 cycles.

2. The electrode according to claim 1, characterized in that: Calculated by mass percentage, in the stainless steel, the Cr content is greater than 5%, and the Ni content is greater than 5%.

3. The electrode according to claim 2, characterized in that: Calculated by mass percentage, the stainless steel comprises the following components: Cr is 16-18%, Ni is 10-14%, Si is 2-3%, Mn is 0-2%, and the balance is Fe.

4. The electrode according to claim 1, characterized in that: In step 1, the stainless steel is pickled with dilute sulfuric acid; the concentration of the dilute sulfuric acid is 1 to 2 mol / L, and the pickling time is 10 to 20 min.

5. The electrode according to claim 1, characterized in that: In step 2, stainless steel and a phosphorus source are placed in a tubular furnace respectively, and the phosphorus source is located upstream of the stainless steel in the tubular furnace, so that the substance obtained by decomposing the phosphorus source at high temperature can react with the stainless steel.

6. The electrode according to claim 1, characterized in that: In step 2, the heating rate is 1-3°C / min.

7. The electrode according to claim 1, characterized in that: The phosphorus source is one of NaH2PO2 and KH2PO2 or a mixture of the two.

8. The electrode according to claim 1, characterized in that: During the electrodeposition process of step 3, the stainless steel electrode was turned over after 10 cycles of electrodeposition and then electrodeposition was performed for another 10 cycles.

9. Application of a high-performance stainless steel-based water electrolysis bifunctional electrode, characterized in that: The electrode according to any one of claims 1 to 7 is used for electrolyzing water and simultaneously evolving hydrogen and oxygen.

Citation Information

Patent Citations

  • Preparation method for phosphatized stainless steel electrolyzed water catalytic material

    CN106486680A

  • Phosphating stainless steel material and preparation method and application thereof

    CN110093623A

  • Ruthenium-loaded amorphous nickel hydroxide / nickel phosphide composite electrode and preparation method and application thereof

    CN113005469A

  • Stainless steel-based catalyst as well as preparation method and application thereof

    CN113481530A

  • Preparation method of electrocatalytic electrolyzed water bipolar plate

    CN114752946A

Cited By

  • Rare earth element doped stainless steel oxygen evolution electrode and preparation method thereof

    CN121046892A